Randomized, blinded, 3-arm clinical trial assessing optimal temperature and duration for treatment with minimally invasive fractional radiofrequency - Alexiades, Macrene; Berube, Dany (Dermatologic surgery, 2015)
A previous multicenter clinical trial of a needle-based fractional radiofrequency (FRF) treatment for facial and neck rhytides and laxity counterintuitively demonstrated a mean target temperature and treatment duration of 69.5 °C and 4.9 seconds for subjects with lesser improvement and 67 °C and 4.2 seconds for greater improvement. To determine optimal temperature and duration settings for maximal clinical results in rhytides and laxity from a single FRF treatment of the face and neck. A randomized, blinded, 3-arm clinical evaluation of FRF at a series of temperatures from 52-57 °C to 67 °C. Three blinded plastic surgeons and dermatologists scored rhytides using the Fitzpatrick Wrinkle Assessment Scale and laxity using the Alexiades Laxity Assessment Scale at 1, 3, and 6 months. Blinded grading showed optimal improvement at 67 °C and 3 seconds and decreased efficacy below 67 °C, with mean rhytide reductions of 40, 29, and 25% and mean laxity reductions of 34, 36, and 25% in Arms 3 (67 °C), 2 (62 °C), and 1 (52 °C-57 °C), respectively. A 100% response rate was observed for all subjects treated at 62 °C to 67 °C target temperature. The optimal target dermal temperature for facial and neck rhytide and laxity treatment is 67 °C and duration of 3 to 4 seconds with a 100% response rate after a single FRF treatment.